Atlas of Pediatric Dermatoscopy (Springer International Publishing, 2018)
This atlas, containing a wealth of clinical and dermoscopic images, describes and illustrates the applications of dermoscopy in a wide variety of skin disorders that may be encountered in the pediatric population. Key features and other salient aspects are highlighted with the aim of enabling the clinician to reach a fast and reliable diagnosis in all cases. Dermoscopy is a non-invasive technique that allows rapid and magnified in vivo observation of the skin, with visualization of morphologic features imperceptible to the naked eye. Dermoscopy has revolutionized the approach to pigmented skin lesions, greatly improving diagnostic accuracy. Furthermore, over the past few years it has been demonstrated to be very useful in the diagnosis, follow-up, and therapeutic monitoring of a range of other skin disorders, including cutaneous/mucosal infections, ectoparasitoses, inflammatory diseases, and hair and nail abnormalities. Being non-invasive, dermoscopy is particularly suitable for use in the pediatric population, in which invasive diagnostic procedures may be problematic.